2017
DOI: 10.1016/j.jaci.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is a critical regulator of type 2 innate lymphoid cells and IL-33 signaling in experimental models of allergic airway inflammation

Abstract: Our findings for the first time demonstrate that ILC2s and IL-33 signaling are regulated by miR-155 in allergic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 46 publications
6
111
1
Order By: Relevance
“…However, others have reported that BM ILC2s are functional in disease models (37, 38). In view of their potential importance, we determined whether BM ILC2s showed sex differences in number, phenotype, or function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have reported that BM ILC2s are functional in disease models (37, 38). In view of their potential importance, we determined whether BM ILC2s showed sex differences in number, phenotype, or function.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial pool of KLRG1 − ILC2s is present in the bone marrow (BM). Whereas one report suggested these cells are ILC2 precursors due to their differentiation to KLRG1 + ILC2s upon adoptive transfer (23), others have shown that BM ILC2s are an important source of type 2 cytokines and mobilized from BM during IL-33–induced inflammation (37, 38). The effects of sex hormones on the functional capacity of KLRG1 − ILC2s in the BM or lungs have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-155 appears to be essential for the development of an eosinophil response, apparently via its capacity to inhibit expression of the transcription factor PU.1, which is a negative regulator of Th2 cytokine production [39]. Furthermore, miR-155 is strikingly up-regulated in type 2 innate lymphoid cells in response to IL-33 and appears to contribute to their expansion [40].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This alteration may be due to the damage induced by the Th2 response, as reduced Th2-dependent eosinophils in allergen-challenged miR-155 KO mice may be restored by the adoptive transfer of OVA-specific CD4+ Th2 cells from OVA-sensitized WT mice [45]. Most recently, a novel mechanism was proposed that miR-155 acts as a key positive regulator in allergen-induced inflammation via type 2 innate lymphoid cell (ILC2s, previously known as natural helper cells) and IL-33 [50]. ILC2s are a type of Th2 cytokine producing cells in airway mucosa [51].…”
Section: The Role Of Mir-155 In Asthmamentioning
confidence: 99%